Mobile Devices in Higher Education, Byod Technology - Badalova, Luiza Kholmamatovna (Miasto Przyszłości, 2023)
Today, a mobile device is not only a means of communication and entertainment, but also a means of education. In the field of education, technology such as BYOD (bring your own device) is emerging and gaining popularity. The article discusses the main aspects of implementing BYOD technology in higher education.